2013
DOI: 10.1111/scs.12035
|View full text |Cite
|
Sign up to set email alerts
|

Associations between family characteristics and public health nurses' concerns at children's health examinations

Abstract: The fact that public health nurses found cause for concern during health examinations was associated with the child's gender, development stage and family characteristic. The research findings may be utilised in planning and targeting health counselling and services in child and school health care. Understanding the role of family characteristics in health and well-being challenges in children is useful in promoting multidisciplinary work in health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
1
13
0
5
Order By: Relevance
“…Detecting and addressing concerns early are key to supporting families and preventing problems . The study by Poutiainen et al . demonstrated that 8.6% of the health examinations of preschool‐aged children raised concerns about their physical health and 5.6% about their psychosocial development.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting and addressing concerns early are key to supporting families and preventing problems . The study by Poutiainen et al . demonstrated that 8.6% of the health examinations of preschool‐aged children raised concerns about their physical health and 5.6% about their psychosocial development.…”
Section: Introductionmentioning
confidence: 99%
“…Collaboration between healthcare professionals is advocated to improve patient outcomes [ 33 ] and enhances the quality of care given to individuals and groups in communities [ 34 ]. Poutianen et al [ 35 ] showed that PCHC nurses’ understanding of the role of family characteristics could be valuable in promoting multidisciplinary work in healthcare. Collaboration between Dutch PCHC and other healthcare professionals exists but still is quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…The support for parenthood is a key mission of the maternity and child health clinic services [ 9 , 10 , 17 – 21 ]. According to earlier studies, parents [ 13 ] and their public health nurses [ 34 ] have frequent worries regarding the health and psychosocial development of child as well as about parenthood. Further, dissatisfaction with the quality of their sexual relationship with their partner, [ 35 ] as well problems in the marital relationship are commonly reported by fathers with small children [ 36 ].…”
Section: Discussionmentioning
confidence: 99%